Local Hyperthermia at 44°C Is Effective in Clearing Cervical High-Risk Human Papillomaviruses: A Proof-of-Concept, Randomized Controlled Clinical Trial. (27th April 2021) - Yang, Yang; Zhang, Lan; Zhang, Yuqing; Huo, Wei; Qi, Ruiqun; Guo, Hao; Li, Xiaodong; Wu, Xin; Bai, Feng; Liu, Kuiran; Qiao, Youlin; Piguet, Vincent; et al.
Abstract: Background: Persistent infection by high-risk human papillomavirus (HPV) is the leading cause of cervical intraepithelial neoplasia and cervical carcinoma. Local hyperthermia at 44ºC has been proven efficacious to clear cutaneous or anogenital warts caused by HPV infection. This study aims to assess the effect of hyperthermia at 44ºC on the clearance of high-risk HPV. Methods: A randomized, patient-blind, sham treatment–controlled trial was conducted in 4 medical centers. We enrolled patients with positive high-risk HPVs and normal or insignificant cytological findings (negative/atypical squamous cells of undetermined significance/low-grade squamous intraepithelial lesion). Participants were randomly assigned (1:1) to receive either hyperthermia at 44ºC or 37ºC, for 30 minutes in each session. Patients in both groups received treatment once a day for 3 consecutive days, plus 2 more sessions 10 ± 3 days later. The primary outcome was clearance rate of HPV 3 months after treatment. Results: After a 3-month follow-up, hyperthermia treatment at 44ºC and 37ºC achieved HPV clearance rates of 85.19% (23/27) and 50% (13/26), respectively ( P  = .014). There was no significant difference of treatment response between patients with single and multiple type of HPV by 44ºC hyperthermia treatment. There were no significant adverse events recorded during the treatment period in both groups. Conclusions: Local hyperthermia at 44ºC safely and significantly aids in clearing cervical high-risk HPVs, the effect of which helps halt the progression of cervical transformation and transmission of the virus. Clinical Trials Registration: NCT03436251. Abstract : Local hyperthermia at 44ºC safely and significantly aids in clearing cervical high-risk human papillomaviruses, the effect of which helps halt the progression of cervical transformation and transmission of the virus.